COMPARISON THE ACCURACY OF COMPUTING POINT COORDINATS BETWEEN DIFFERENT INSTRUMENTS AND APPLICATIONS OF GPS - & et al., Abdulwadood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The study was aimed to determine the coordinates of  the points were measured by different ways and different instruments, the most precise way using the differential global positioning system (DGPS) that will be the reference measurements in comparison, less precise way using navigator GPS. Google earth (pro.), and the other applications of GPS mobile ( Samsung and I-phone). In this research (8 points) were chosen that are occasional in location. The comparison of the different observations can give us an idea of ​​the extent to which the accuracy of the observations differs from the different devices used in the observing, as well as through the knowledge of the best device and the best way to measure coordinates accurately to serve the desired purpose.